Seaweed Farmers Perceptions of Children's Formal Education Level in Bulu-Bulu Village, Tonra District, Bone Regency - Maddatuang, Maddatuang; Suprapta, Suprapta; Winarti, Wildi (UNIVERSITAS NEGERI MAKASSAR, 2021)
This research is a descriptive study that aims to: 1) Knowing the condition of formal education for the children of seaweed farmers in Bulu-Bulu Village. 2) Know how seaweed farmers' perceptions of the level of formal education of children in Bulu-Bulu Village, Tonra District, Bone Regency. 3) Knowing what factors influence the perceptions of seaweed farmers on the level of formal education of children in Bulu-Bulu Village. The population ini this study was 114 housedhold heads. The sampling technique used the Snowball Sampling technique with a sample size of 30 household heads. Data collection was carried out by means of observation, interviews, and documentation. Data analysis technique using descriptive statistical analysis techniques.The results of this study indicate that the most of the formal education conditions of the children of seaweed farmersÂ in the village of Bulu-Bulu, Tonra subdistrict, are mostly still continuing their education at the primary and secondary levels. Perception of seaweed farmers on the level of formal education of children in Bulu-Bulu Village, Tonra District is quite good (positive). Seaweed farmers' perceptions of the level of formal education of children are influenced by factors such as education level, income level, and workload.